ANALISIS TITIK PULANG POKOK USAHA BAWANG GORENG PADA IKM SAL-HAN DI KOTA PALU - Gabriella, Fransisca; Effendy, Effendy (AGROTEKBIS, 2018)
Palu fried onion is one of the leading commodity in Palu. Unlike the other onions from outside of Palu city, fried onions from Palu, Sigi, and even Donggala have a unique taste and aroma. This researchwas aimed to find out the Break Even Point of  Fried Onions business at      Sal-Han SMI. The research was conducted for 2 months from March to April 2017 at Sal-Han SMI. Respondents were 3 persons, Owners of Sal-Han SMI and 2 permanent employees. Data analysis  using is the Break Even Point Analysis with 5 types of packaging, which is packing 60 gram, packing 100 gram, packing 120 gram, packing 200 gram and packing 500 gram. The results showed that Break Even Point for packing of 60 gram was achieved on the production volume of 185 packs,at that point obtained revenue of IDR 2,960,000.The Break Even Point for 100 gr of packaging were achieved on the production volume of 221 packs, at that point obtained revenue of IDR 5,304,000. The Break Even Point for 120 gram of packaging were achieved on the production volume of 162 packs,at that point obtained revenue of IDR 4,860,000. The Break Even Point for 200 gram of packaging is achieved on the production volume of 120 packs,at that point obtained revenue of IDR 5,760,000. The Break Even Point for 500 gram of packaging is achieved on the production volume of 36 packs, at that point obtained revenue of IDR 4,320,000.